Penerapan Live Worksheet pada Model Pembelajaran Flipped Learning untuk Meningkatkan Hasil Pembelajaran Peserta Didik - Ponco Dewi Retno (Jurnal Didaktika Pendidikan Dasar, 2022)
Learning at SD N 6 Getas in a pandemic condition is carried out online, but the activeness of students in learning is low which causes student learning outcomes to be low, so it is necessary to research the application of live worksheets in the flipped learning model to improve student learning outcomes. The purpose of this study was to determine the increase in student learning outcomes and to know the implementation of learning by applying a live worksheet to the flipped learning model. This research is a classroom action research with the subjects of this research are students in grade 5 SD N 6 Getas, Kec. Singorojo Kendal academic year 2020/2021. This research in the subject of action is mathematics material building space. The research instruments included teacher observation sheets, students, test questions, and documentation. The results of this study are the application of a live worksheet in the flipped learning model can improve student learning outcomes, this is evidenced by the increase in learning outcomes in cycle 1 and cycle 2. In cycle 1 achieved 75% classical completeness with an average of 75, and cycle 2 reached 84% with an average of 80.5. The conclusion of this study is that the application of a live worksheet in the flipped learning model can improve student learning outcomes.